2021
DOI: 10.1055/s-0041-1740607
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hindlimb Deformity and Posture in Dogs with Grade 2 Medial Patellar Luxation during Awake Computed Tomography Imaging while Standing

Abstract: Objective The aim of this study was to determine the degree of bone deformities and hindlimb postural abnormalities in a standing position in awake Toy poodles with and without grade 2 medial patellar luxation (MPL) using high speed 320-row computed tomography (CT). Methods The limbs with grade 2 MPL (MPL-G2 group) and without any orthopaedic disorders (control group) were imaged in a standing position, without sedation or anaesthesia, using CT. In MPL-G2 group, images were obtained when the patella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Using this technology, investigators from Japan studied Toy Poodles with grade two medial patellar luxation while the dogs were awake and standing. 1 Their studies indeed confirmed that these dogs lacked any significant bone deformity. However, with the patella medially luxated, there were marked standing postural abnormalities of the hindlimb.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Using this technology, investigators from Japan studied Toy Poodles with grade two medial patellar luxation while the dogs were awake and standing. 1 Their studies indeed confirmed that these dogs lacked any significant bone deformity. However, with the patella medially luxated, there were marked standing postural abnormalities of the hindlimb.…”
mentioning
confidence: 72%
“…These included external rotation of femur, internal rotation of tibia and foot, large stifle joint convergence angle, genu varum and toe-in standing in dogs with a grade two medial patellar luxation. 1 The genu varum stance was associated with 30 degrees of internal rotation of the tibia, relative to the distal femur. Clinically this 'bow-legged' stance could be mistaken for distal femoral varus and a medial deformity of the tibial tuberosity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Medial patellar luxation typically accompanies varus deviation of the distal femur, valgus of the proximal tibia, external torsion of the tibia and malposition and incorrect development of the quadriceps musculature. 6…”
Section: Introductionmentioning
confidence: 99%
“…5 Medial patellar luxation typically accompanies varus deviation of the distal femur, valgus of the proximal tibia, external torsion of the tibia and malposition and incorrect development of the quadriceps musculature. 6 Classically, surgical correction of medial patellar luxation is recommended in adult patients without active physeal lines or young adults who are close to skeletal maturity. 3,7 However, maintenance of bone deformities while the physeal lines remain open and functional can generate even more pronounced bone deviations, culminating in the progressive worsening in these patients.…”
Section: Introductionmentioning
confidence: 99%